2017
DOI: 10.1007/s13205-017-0678-9
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profile and free radical nitric oxide (NO) scavenging activity of Averrhoa bilimbi L. fruit extract

Abstract: Averrhoa bilimbi L. belongs to family Oxalidaceae. Traditionally, people use this plant (root, bark, leaves and fruits) for treating several illnesses include itches, boils, syphilis, whooping cough, hypertension, fever and inflammation. The aim of the study was to evaluate the nitric oxide (NO) scavenging activity and GC-MS analysis of A. bilimbi L. fruit extract. Averrhoa bilimbi L. fruits were collected for the preliminary phytochemical analysis, antioxidant scavenging activity and biologically important co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
1
14
0
1
Order By: Relevance
“…This inhibitory activity is slightly comparable to that of the plant extracts reported by Adebayo et al. (2019) and lower than the value reported by Suluvoy and Berlin Grace (2017) for Averrhoa bilimbi L. fruit extract. FRAP assay measures the ability of any compound to convert Fe 3+ to its reduced state Fe 3+ , which is an indicator of total antioxidant capacity of such compound ( Haida and Hakiman, 2019 ).…”
Section: Discussionsupporting
confidence: 71%
“…This inhibitory activity is slightly comparable to that of the plant extracts reported by Adebayo et al. (2019) and lower than the value reported by Suluvoy and Berlin Grace (2017) for Averrhoa bilimbi L. fruit extract. FRAP assay measures the ability of any compound to convert Fe 3+ to its reduced state Fe 3+ , which is an indicator of total antioxidant capacity of such compound ( Haida and Hakiman, 2019 ).…”
Section: Discussionsupporting
confidence: 71%
“…The noted antioxidant activity is correlated to the phenolic profile of H. tuberosus . Concentration-dependent antioxidant and free radical scavenging activities have been reported in many phenolic-rich phytocompounds [ 33 ]. Overall, it could be suggested that the phenolic-based phytocompounds present in the active fraction of the H. tuberosus reduced the oxidative-stress-mediated complications in diabetic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Various damages were found in the midgut, especially in the epithelium cells, microvilli, and basal membrane. These damages were due to larvicidal compounds contained in A. bilimbi fruit extract, which were saponins [8] that explained that Averrhoa bilimbi fruits contained saponins. Saponins have potential as larvicide and work as stomach poison in Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Extract of A. bilimbi flower could induce changes in the midgut of Anopheles barbirostris larvae, causing damage on peritrophic membrane, epithelium cells, and basal membrane, and saponins enter the larvae body through the digestive tract; thus, it can function as stomach toxin that disrupts nutrition absorption. Other compounds, terpenoids, are antifeedant that averse larvae to feed, consequently inducing mortality [8]. Extract of A. bilimbi leaf and fruit could damage the villi and cause malformation of the epithelium cells in the midgut of Ae.…”
Section: Discussionmentioning
confidence: 99%